Perancangan Aplikasi Lajena (Pelaporan Angka Bebas Jentik Nyamuk) Secara Online Mendukung Gerakan Satu Rumah Satu Jumantik Menggunakan Metode Waterfall Di Puskesmas Kedungmundu Kota Semarang - Aisah, Rika Nur; Haikal, Haikal (Pena Medika Jurnal Kesehatan, 2023)
The Covid-19 pandemic has made it impossible to carry out the activities of examining mosquito larvae directly in people's homes. So that the reporting of mosquito larvae is done through the WhatsApp group. Each home must report the status of the larvae in their respective homes. This is considered less objective, because there is no cross- examination. During the Covid-19 pandemic, we learned that there are conditions under which people have to limit their activities and mobility. The purpose of designing this app is that larvae tracking should be more accurate and precise and can help solve the larva-free numbers problem in the Kedungmundu Health Center area.This type of research is qualitative research with descriptive analysis using the Waterfall method. Subject was imaged using intentional sampling technique at 5 Jumantic Cadres, 1 P2DBD program leader at Kedungmundu Health Center, and 5 One House One Jumantic Cadres. The subject of this study is the examination of mosquito larvae.The results is the design of the LAJENA (Mosquito Larva-Free Numbers Report) application in the form of design analysis in form of a flowchart, decomposition diagram, data and database flowchart and user interface in the form of Appearance of the application in the form of login and registration pages, dashboard pages, reporting pages, and report history pages that conform to user needs for user needs to independently report maggot examination.